Cellobiose-dehydrogenase production by some fungal species isolated in rain forests of Northern Vietnam - Dinh Giap, Vu; My Hiep, Thai Thi; Huu Nghi, Do (Vietnam Journal of Biotechnology, 2020)
Fungal enzymes are well-known as effective in hydrolyze lignocellulose-rich materials. This decomposition process requires many enzymes to participate in a coordinated factor to hydrolyze the polymer structure. Among them, there are some of popular oxidized enzymes such as lignin peroxidase, mangan peroxidase and laccase. Cellobiose dehydrogenase (CDH) is an extracellular enzyme found in various fungi, it was first discovered in 1974 by Westermark in white rot fungus Trametes verscolor and Phanerochaete chrysosporium. The biological role of CDH has been proven to participate in the decomposition of natural polymers such as cellulose, hemicellulose and lignin by generating hydroxyl radical through Fenton reaction. CDH has unique biochemical and catalytic properties that have been used in biosensors to detect cellodextrin, maltose, lactose and diphenol compounds or in biomedical applications such as lactobionic acid production. Therefore, CDH is an important component of the extracellular enzyme system for lignocellulose decomposition.  In this study, 47 fungal strains isolated from rainforests of Cuc Phuong and Muong Phang National Parks and screened for CDH activity. Of which, 33 active fungi exhibited CDH activity from 8.89 to 74.4 U/L during growth on solid medium with rice straw as raw substrate. The highest enzyme production was identified for Coprinellus aureogranulatus (MPG14) reach 77.4 U/L on basic medium and its CDH activity of up to 237.4 U/L under optimal condition: supplemented with carbon source of α- cellulose (20 g/L), nitrogen source (5 g/L peptone) incubated for 12 days at 30℃, pH 5.5 and 200 rpm after inoculation.     Thus, the fungus has the potential to exploit the CDH enzyme applied in the pretreatment of lignocellulose-rich materials.